World history from and Islamic perspective: the experience of the International Islamic University Malaysia - Abu Shouk, Ahmed Ibrahim (IIUM Press, 2009)
The contemporary call for Islamization of knowledge is a revivalist response to modernity and its secular impact on Muslim society and educational institutions. It stems from the premise that contemporary knowledge is neither value-free nor universal. It has been designed by Western scholars who frame the world from their own distinct cultural, historical and secular perspective. This call was popularized and developed by Ismail Raji al-Faruqi into a set of principles and work-plan that triggered a series of scholarly debates and discussions on the Islamic approach to knowledge and education. This article attempts to examine the rationale of the Islamization of knowledge and its application at the International Islamic University Malaysia (IIUM) with a particular emphasis on the history and civilization programmes that aim at encouraging students to cultivate and Islamic perspective through which they will be able to enhance their intellectual understanding of continuity and change in world history and civilization dialogues across religions and nations.